Method to quantify aluminum-induced organic acids secretion by roots of plants in nutrient solution using GC–MS - de Oliveira Carvalho Bittencourt, Brenda Mistral [UNESP]; Filho, Sebastião Zanão [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2020)
Organic acids (OAs) play an essential role in several cellular biochemical pathways. Released by plant roots, OAs can help them tolerate phytotoxic forms of aluminum (Al) present in acidic soils. Some studies use high-performance liquid chromatography (HPLC), ion chromatography and, more rarely, gas chromatography-mass spectrometry (GC–MS) to analyze exuded OAs, but they are limited to hours or 1–2 days. The main limitation is that OAs are measured only in CaCl2 and AlCl3 solutions, and not in “complete” nutrient solutions, only enabling short-term collection of secreted OAs. Here, we aimed to test a method to quantify citric, malic, oxalic and succinic acids in “complete” nutrient solution with 0, 740 and 1480 μM Al, using a GC–MS. First, a calibration curve was established through a chromatogram that was generated using six concentrations of OAs in methanol. Thus, samples containing OAs only were derived by methylation. Then, analytical curves were set up using seven OAs concentrations added in the three nutrient solutions. The OAs were concentrated by drying the solutions. After re-suspension, samples were derived by methylation. Instrumental precision and the method repeatability were also checked. Chromatograms showed adequate resolution, with distinct peak heights between OAs concentrations and their respective retention times. Both calibration and analytical curves indicated consistent linearity (R > 0.99), evidencing the method and equipment parameters were able to provide results directly proportional to OAs concentrations. This low-cost method is recommended for evaluation of Al-induced OA secretion by roots of whole plants in nutrient solutions for several days or weeks.
Keywords: Al-tolerance; Citric acid; Exudation; Malic acid; Oxalic acid; Succinic acid